Self-maintenance of zonal hepatocytes during adult homeostasis and their complex plasticity upon distinct liver injuries - Chow Hiang Ang; Philip Arandjelovic; Jinming Cheng; Jicheng Yang; Fusheng Guo; Yuanquan Yu; Sarmilla Nelameham; Lachlan Whitehead; Jiangtao Li; David L. Silver; Nick Barker; Jane E. Visvader; et al. (Cell Reports)
Summary: Hepatocytes are organized into distinct zonal subsets across the liver lobule, yet their contributions to liver homeostasis and regeneration remain controversial. Here, we developed multiple genetic lineage-tracing mouse models to systematically address this. We found that the liver lobule can be divided into two major zonal and molecular hepatocyte populations marked by Cyp2e1 or Gls2. Pericentral Cyp2e1+ and periportal Gls2+ hepatocytes maintain their own lineage during adult homeostasis, while Cyp2e1+ hepatocytes fuel neonatal liver growth. The Gls2+ and Cyp2e1+ populations can rapidly regenerate one another when one of the populations is severely damaged. Midlobular Ccnd1+ hepatocytes are enriched in the Cyp2e1+ zone in adult liver but have limited contributions to regeneration upon partial hepatectomy and severe pericentral injury. Remarkably, Lgr5+ hepatocytes, a unique Cyp2e1+ subset, contribute significantly to liver replenishment upon periportal injuries. Our findings unravel that zonal hepatocytes mainly self-maintain during homeostasis but exhibit complex plasticity in repair upon injury.